1994
DOI: 10.1001/archinte.154.11.1261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beef and chicken consumption on plasma lipid levels in hypercholesterolemic men

Abstract: In this short-term study, comparably lean beef and chicken had similar effects on plasma levels of total, low-density lipoprotein, and high-density lipoprotein cholesterol and triglyceride. We concluded that lean beef and chicken are interchangeable in the Step I Diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Total, LDL, and HDL cholesterol fell significantly, and TG did not change over a 5-week intervention period [19]. Davidson et al [20] conducted a similar study and reported results consistent with those of Scott et al [19], with the exception of a small (2%) but significant increase in HDL cholesterol in both the beef and chicken groups. Furthermore, they carried the study out for 36 weeks and found that the cholesterol-lowering effects of lean red and white meats persisted for the duration of the study.…”
Section: Plasma Lipids and Lipoproteins: Clinical Studiesmentioning
confidence: 71%
See 2 more Smart Citations
“…Total, LDL, and HDL cholesterol fell significantly, and TG did not change over a 5-week intervention period [19]. Davidson et al [20] conducted a similar study and reported results consistent with those of Scott et al [19], with the exception of a small (2%) but significant increase in HDL cholesterol in both the beef and chicken groups. Furthermore, they carried the study out for 36 weeks and found that the cholesterol-lowering effects of lean red and white meats persisted for the duration of the study.…”
Section: Plasma Lipids and Lipoproteins: Clinical Studiesmentioning
confidence: 71%
“…Incidentally, lean red meats are low in these fatty acids, and thus would not be expected to adversely affect blood lipids. Scott et al [19] demonstrated that NCEP Step 1 diets containing beef (85 g; 8% fat) or chicken (85 g; 7% fat) have similar cholesterol-lowering effects in hypercholesterolemic individuals. Total, LDL, and HDL cholesterol fell significantly, and TG did not change over a 5-week intervention period [19].…”
Section: Plasma Lipids and Lipoproteins: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the cholesterol-raising potential of meat products appears to be a function of their fat and cholesterol contents [3], substituting leaner selections of red or white meat for higher-fat cuts of meat should favorably influence serum total and LDL cholesterol levels [12]. Scott et al [3,4] reported results supporting this hypothesis. In two randomized controlled feeding studies, these researchers compared blood lipid responses to the consumption of lean beef versus chicken and fish, or chicken alone, among hypercholesterolemic men.…”
Section: Historical Overviewmentioning
confidence: 99%
“…As part of suggested dietary changes, medical professionals frequently counsel patients with hypercholesterolemia to limit or eliminate intake of red meats, despite evidence from controlled diet studies that lean red meat (LRM) and lean white meat (LWM) have similar effects on the serum lipid profile [3,4]. This article summarizes the results of a 36-week randomized multisite dietary intervention trial recently reported in Archives of Internal Medicine [5].…”
mentioning
confidence: 99%